PENGARUH HALAL AWARENESS TERHADAP MINAT BELI KONSUMEN PRODUK MINUMAN KOREAN SPARKLING WATER MOJISO (Studi Pada Mahasiswa Muslim Penggemar Drama Korea) - Cynthia Renita Putri; Nur Diana; Harun Al Rasyid (El-Aswaq, 2020)
This study was to determine the effect of Halal Awareness on Interest Buy consumer Korean beverage products Sparkling Water Mojiso. This type of research is correlational quantitative research. In this study, the samples taken were Muslim students who were fans of Korean dramas in Malang City who knew and were interested in buying Korean products Sparkling Water Mojiso, which numbered 95 people. Taking the number of samples using the Non Probability technique Sampling with Accidental Approach Sampling to obtain respondents. The analytical tool used is analysis Simple Linear Regression using SPSS 25 tool. The results showed that the t value was 5.247 with a significance of 0.000 the value was < 0.05, which means Ho is rejected and Ha is accepted. This means that the Halal Awareness (X) variable partially has a positive and significant effect on Buying Interest (Y) of Consumer Products Korean Sparkling Water Mojiso Drink.